Mast Cells Drive Systemic Inflammation and Compromised Bone Repair After Trauma - Ragipoglu, Deniz; Bülow, Jasmin; Hauff, Kristin; Voss, Martin; Haffner-Luntzer, Melanie; Dudeck, Anne; Ignatius, Anita; Fischer, Verena (Frontiers in Immunology, 2022)
There is evidence that mast cells contribute to inflammation induced by hemorrhagic shock, severe tissue injury or sepsis. Mast cells are highly responsive to alarm signals generated after trauma, and release many inflammatory mediators including interleukin-6, a key mediator of posttraumatic inflammation. An overwhelming posttraumatic inflammation causes compromised bone healing; however, the underlying cellular and molecular mechanisms are poorly understood. Recently, we found that mast cells trigger local and systemic inflammation after isolated fracture leading to uneventful bone repair. Here, we investigated whether mast cells critically contribute to trauma-induced compromised bone healing. Male Mcpt5-Cre+ R-DTA mice, which lack connective tissue type mast cells, and their MC-competent Cre− littermates underwent a femur fracture with/without thoracic trauma. Posttraumatic systemic and local inflammation and bone repair were assessed 3 h and 21 d post injury. Both, the systemic and pulmonary inflammation was significantly increased in mast cell-competent mice upon combined trauma compared to isolated fracture. In mast cell-deficient mice, the increase of inflammatory mediators in the circulation induced by the severe trauma was abolished. In the bronchoalveolar lavage fluid, the trauma-induced increase of inflammatory cytokines was not reduced, but the neutrophil invasion into the lungs was significantly diminished in the absence of mast cells. Locally in the fracture hematoma, mast cell-competent mice displayed reduced inflammatory mediator concentrations after combined trauma compared to isolated fracture, which was abolished in mast cell-deficient mice. Notably, while combined trauma resulted in compromised bone repair in mast cell-competent mice, indicated by significantly reduced bone and increased cartilage fracture callus contents, this was abolished in Mcpt5-Cre+ R-DTA mice. Therefore, mast cells contribute to trauma-induced compromised bone repair and could be a potential target for new treatment options to improve fracture healing in multiply injured patients.